1982
DOI: 10.1128/iai.36.2.775-781.1982
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma arthritidis-induced ocular inflammatory disease

Abstract: Mycoplasma arthritidis was demonstrated to incite experimental conjunctivitis and uveitis in Swiss Webster mice which have a known susceptibility to the arthritis customarily associated with infection by this mycoplasma. The initial symptom of ocular involvement was conjunctivitis, which appeared as early as 1 day after intravenous injection with viable culture concentrates of M. arthritidis. By day 2, histological analysis showed intraocular localized inflammatory reactions that were confined primarily to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…We have confirmed previous work (6,17,18) which indicated that M. arthritidis is toxic for w A 0 mice after systemic administration. In addition, the present studies have shown pronounced differences in the susceptibility of different CS t > mouse strains to the toxic syndrome.…”
Section: Discussion Osupporting
confidence: 92%
See 1 more Smart Citation
“…We have confirmed previous work (6,17,18) which indicated that M. arthritidis is toxic for w A 0 mice after systemic administration. In addition, the present studies have shown pronounced differences in the susceptibility of different CS t > mouse strains to the toxic syndrome.…”
Section: Discussion Osupporting
confidence: 92%
“…injection of organisms, fibroplasia and collagen synthesis induced by local lymphokine release (12,16,19) are more likely explanations. Although eye cultures were not performed in our studies, Thirkill and Gregerson (17) reported that only 2 of 20 involved eyes yielded mycoplasmas by culture, suggesting that ocular involvement was not dependent on a direct infectious process. Preliminary attempts to protect responsive (C3H) mice against the toxic effects of M. arthritidis by immunizing them with mitogen-containing supernatants of M. arthritidis failed (unpublished data).…”
Section: Discussion Omentioning
confidence: 65%
“…Mycoplasma-induced anterior uveitis. Two liters of PPLO broth (Difco Laboratories, Detroit, Mich.) supplemented with 10% horse serum-5% fresh yeast extract and containing 100 U of penicillin G per ml was inoculated with 10 ml of a 48-h culture of M. arthritidis strain 158 PloP9 (15) and then incubated aerobically at 37°C for 3 days. Centrifugation at 10,000 x g at 4°C for 30 min produced a pellet which was washed twice in sterile phosphate-buffered saline (PBS) before being suspended to a total of 2 ml and assayed for viable, colony-forming units.…”
Section: Methodsmentioning
confidence: 99%
“…Purification of arginine deiminase. A 6-liter volume of M. arthritidis was cultured and harvested as described previously (15). The pellet was suspended to a total of 2 ml in PBS, pH 7.5, sonicated in ice to produce a homogenate, and centrifuged at 10,000 x g for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…39 Mycoplasma pulmonis and M. arthritidis may cause respiratory, eye and joint-related conditions and may affect reproduction, at least if enhanced by other factors. 21,[40][41][42][43][44][45] However, even in the absence of clinical symptoms, it may have impact on certain models. [46][47][48][49][50] Filobacterium rodentium (formerly known as cilia-associated respiratory (CAR) bacillus 51 ), while usually asymptomatic, 52 is the cause of chronic respiratory disease in rats, 53,54 and BALB/c mice.…”
Section: Introductionmentioning
confidence: 99%